Broken heartland : the rise of America's rural ghetto - Davidson, Osha Gray (University of Iowa Press, 1996)
Between 1940 and the mid 1980s, farm production expenses in America's Heartland tripled, capital purchases quadrupled, interest payments jumped tenfold, profits fell by 10 percent, the number of farmers decreased by two-thirds, and nearly every farming community lost population, businesses, and economic stability. Growth for these desperate communities has come to mean low-paying part-time jobs, expensive tax concessions, waste dumps, and industrial hog farming, all of which come with environmental and psychological price tags. In Broken Heartland, Osha Gray Davidson chronicles the dec.